Envelhecimento e afetividade de idosos em situação de violência - Santos, Letícia Souza dos (Brasil, 2024)
The aging of the population and the increase in life expectancy are due to social and technological factors. Currently, in the Brazilian context, there is a growth in the elderly population, and proportionally, an increase in cases of violence against the elderly. The impact of violence against this population on affective-cognitive functioning is still little explored. This study aims to analyze the affective-cognitive functioning of elderly people in situations of violence, based on standardized psychological assessment instruments, such as the Pfister Colored Pyramid Test (TPC), Geriatric Depression Scale (GDS) and Geriatric Anxiety Inventory (GAI). The research was conducted with 15 elderly people aged 60 and over, served by the Integrated Center for the Protection and Defense of the Elderly (CIPDI), of the State Secretariat of Justice, Human Rights and Citizenship (SEJUSC). The study method was exploratory research, with multiple case studies with elderly individuals, based on psychological assessment of affective-emotional aspects. The instruments used were the Identification Form of the Integrated Center for the Protection and Defense of the Elderly (CIPDI), MINI MENTAL STATE EXAMINATION (MMSE), Geriatric Depression Scale, Geriatric Anxiety Inventory and Pfister Colored Pyramids Test. From the research, indicators of mild depression and indicators of moderate anxiety were found in the elderly participants, in addition, from the results of the TPC, it is possible to infer about the emotional dynamics of elderly individuals in situations of violence.